Assessment of respiratory morbidity among loading and unloading workers exposed to cement dust - Krishna, Lalu; Pandarikkal, Jagadees R.; Sreedharan, Ranjith; Sampson, Ursula; Annamala, P. T.; Unni, Kumudam M. (International Journal of Research in Medical Sciences, 2019)
Background: A higher incidence of occupational diseases has been reported recently compared to the past years. One of the industries where workers are remarkably exposed to dust is cement industry. Several studies have been conducted to evaluate pulmonary functions and biochemical parameters of workers exposed to cement dust in factories and construction sites, but few were concentrated among loading and unloading workers of warehouses. Hence the present study was undertaken to find out the effect of cement dust among loading and unloading workers of cement warehouses. Methods: This study was conducted among 82 exposed (cement dust) and 82 non-exposed individuals. Frequency of symptoms, biochemical parameters and spirometric values were taken from all subjects. Spirometric parameters recorded were, forced vital capacity (FVC), Forced expiratory volume (FEV1), FEV1/FVC% and Peak expiratory flow rate (PEFR). Results: Out of exposed group, 51.2% had cough, 46.3% had rhinitis 45.2% had breathlessness. FEV1 and FVC showed significant reduction while FEV1/FVC values were normal. No significant changes were seen in renal function tests or liver function tests. Mean value of erythrocyte sedimentation rate (ESR) was found to be significantly increased. Conclusions: Compared to normal healthy adults the loading and unloading workers in cement warehouses showed restrictive lung disease and an increase in ESR representing a non-specific inflammatory change. A continuous bio monitoring of health status must be initiated for these employees and awareness campaigns regarding the exposure and use of standardized protective devices must be mandated.